(untitled) (Eurasian Journal of Ecology, 2021)
The main results of the work on the study of the applicability of bacterial lux-biosensors for genotoxicological studies are presented. Biosensors are strains of E. coli MG1655 carrying a recombinant plasmid with the lux-operon of the luminescent bacterium P. luminescens, transcriptionally fused with promoters of inducible genes of the genes: recA, colD, dinI, alkA, soxS, and katG. The genotoxicity of 47 chemical compounds was tested on a set of three biosensors pSoxS-lux, pKatG–lux and pColD–lux, which allows to evaluate the oxidant and DNA-damaging activity of the studied drugs. A comparison of the results obtained with the data on the mutagenic activity of these drugs in the Ames test showed a complete coincidence of the results for 42 substances. The study of the modifying effect of 29 antioxidants and radioprotectors on the genotoxic effects of chemical agents showed the applicability of a pair of biosensors pSoxS-lux and pKatG-lux for the primary assessment of the potential antioxidant and radioprotective activity of chemical compounds. For the first time, using lux-biosensors, an enhancing effect of the heavy non-radioactive isotope of hydrogen deuterium (D2 O) on the genotoxicity of chemical compounds has been discovered and the probable mechanisms of this action have been studied. Thus, the results obtained showed that lux-biosensors can be successfully used to identify potential genotoxicants, radio-protectors, antioxidants, and comutagens among chemical compounds, as well as to study the probable mechanism of genotoxic action of the studied substance. Key words: lux-biosensors, E. coli, drugs, chemical agents, environmental pollutants, genotoxicity, antioxidants, deuterium.